The Plea Discount and the Time Penalty in Canada: impacts of the Guilty Plea at Sentencing - Johnson, Brendyn (Canadian journal of criminology and criminal justice, 2023)
The plea discount (or trial penalty) refers to disparity in sentencing resulting from the decision to plead guilty or proceed to trial. It is often suggested that pleading guilty reduces one’s odds of being imprisoned or reduces the length of one’s sentence. While plea discounts haves been studied extensively in the United States, there is very little indication in Canada as to their existence or scope. Using data from the Integrated Criminal Court Survey (N = 2,198,954), this study analyzes logit-negative binomial hurdle models to study the plea discount in Canadian criminal courts and how it varies by court resource usage. It finds that the probability of being incarcerated is nominally higher after pleading guilty, but that pleading guilty reduces custodial sentence length. Further, it finds that the amount of resources used to resolve a case moderates the impact of a guilty plea in both situations.